Near-infrared intraoperative imaging of pancreatic neuroendocrine tumors: a new era in laparoscopic pancreatic surgery - Doi, Ryuichiro; Toyoda, Eiji; Kitaguchi, Kazuhiko; Abe, Yusuke; Hirose, Tetsuro (Laparoscopic Surgery, 2018)
It is evident that safe complete resection of the target tumor without excess or deficiency is the most important object in the oncological surgery, besides this is particularly true in the laparoscopic surgery for pancreatic neuroendocrine tumors (PanNETs).